TOX regulates T lymphocytes differentiation and its function in tumor - Niu, Haiyue; Wang, Huaquan (Frontiers in Immunology, 2023)
Thymocyte selection-associated high mobility group box protein (TOX) is expressed differently at all T cell development stages. Owing to more advanced scientific and technological means, including single-cell sequencing technology, heterogeneity of T cells and TOX has gradually been revealed. Further exploration of such heterogeneity will help us comprehend the developmental stage and functional characteristics of T cells more deeply. Emerging evidence supports its regulation not only in exhausting, but also in activating T lymphocytes, verifying TOX heterogeneity. TOX can be used not only as a latent intervention target for tumor diseases and chronic infections, and a therapeutic strategy for autoimmune diseases, but also as a critical factor predicting the drug response and overall survival of patients with malignant tumors.